Field and Gaussian-based 3D-QSAR models on 8-amino-imidazo [1, 5a] pyrazine derivatives as Bruton’s tyrosine kinase inhibitors - Seethalakshmi Sakthivel, Julie Rebecca Joseph Mathari, Mursaleen Baba, Habeeb Shaik Mohideen (Journal of Applied Pharmaceutical Science, 2025)
Bruton’s tyrosine kinase (BTK) stands as a crucial enzyme implicated in various health disorders associated with B-cells, garnering significant attention over time. It presents a compelling molecular target for addressing autoimmune diseases and malignancies linked to B-cells. The inhibition of BTK has demonstrated efficacy in treating autoimmune diseases, B-cell leukemia, and lymphomas. In this study, we conducted a 3D-QSAR analysis on a series of derivatives of 8-Amino-imidazo [1, 5a] pyrazines and optimized CGI-1746 derivatives to pinpoint essential descriptors that augment their biological activity. Our study involved the creation of Gaussian and field-based 3D-QSAR models using target-based alignment derived from docked poses. These models exhibited statistical validity, with a predictive correlation coefficient (q2) of 0.67 for the Gaussian model and 0.60 for the field-based model. Additionally, conventional correlation coefficients (r2) were 0.93 and 0.92 for the Gaussian and field-based models, respectively. Contour map analyses unveiled the significance of steric and hydrophobic interactions as substantial contributing factors to the enhanced activity of these compounds. These discoveries hold significant promise for advancing research and development in the realm of BTK inhibitors.
Keywords: Autoimmune diseases, pyrazine derivatives, structural bioinformatics, 3D-QSAR